State-Dependent Synchrony and Functional Connectivity in the Primary and Secondary Whisker Somatosensory Cortices - Khateb, Mohamed; Schiller, Jackie; Schiller, Yitzhak (Frontiers in Systems Neuroscience, 2021)
Synchronized activity plays an important role in sensory coding and memory and is a hallmark of functional network connectivity. Yet the effect of sensory activation on synchronization and cortical functional connectivity is largely unknown. In this study, we investigated the effect of whisker activation on synchronization and functional connectivity of the primary (wS1) and secondary (wS2) whisker somatosensory cortices at the single-cell level. During the spontaneous pre-stimulus state neurons tended to be functionally connected with nearby neurons that shared similar tuning characteristics. Whisker activation with either ramp-and-hold stimulation or artificial whisking against sandpaper significantly reduced the average overall pairwise synchronization and functional connectivity within the wS1 barrel and wS2 cortices, with whisker stimulation disconnecting approximately a third of neuronal pairs that were functionally connected during the unstimulated state. Nearby neurons with congruent tuning properties were more likely to remain functionally connected during whisker activation. Our findings indicate cortical somatosensory networks are organized in non-random small world networks composed of neurons sharing relative similar tuning properties. Sensory whisker activation intensifies these properties and further subdivides the cortical network into smaller more functionally uniform subnetworks, possibly serving to increase the computational capacity of the network.